Practice of self-medication to manage oral health issues in a community setting of Nepal - Ashish Shrestha; Tarakant Bhagat; Santosh Kumari Agrawal; Ujwal Gautam; Naresh Prasad Joshi (BMC Oral Health)
Abstract Background Self-medication has been defined as the practice of self-diagnosis and medication use without seeking professional healthcare advice. Its prevalence for alleviating dental problems in Nepali communities has not been explored. This study was conducted to assess self-medication for oral health problems in a community setting in Nepal. Methods A community-based cross-sectional study was conducted in two conveniently selected wards of Baraha Municipality of Sunsari district in August 2021 using a pre-validated questionnaire in the Nepali language. The prevalence of self-medication for oral health problems was assessed. The chi-square and Mann-Whitney U tests were used to check its association with demographic variables. Results The prevalence of self-medication was found to be 43.3%. The most common health problem leading to self-medication was toothache (78.5%). Around half of the respondents (55.1%) replied achieving temporary relief after its use while around a quarter (25.1%) thought that self-medication was effective in taking care of their problems. Three-quarters of the respondents (75.7%) knew that they had to visit a dentist if their problems persisted. The annual family income was significantly associated with the practice of self-medication for oral health problems. (p = 0.013) Conclusion Self-medication was found to be frequently utilized by the people of Baraha municipality with almost every second person with oral health problems reporting using it to solve their problems. This phenomenon is disproportionately seen in those with lower economic status. Clinical trial number Not applicable.